Development of Novel Nomograms to Predict 5- and 7-Year Biochemical-Recurrence-Free Survival in High-Risk Prostate Cancer Patients After Carbon-Ion Radiotherapy and Androgen Deprivation Therapy - Takanobu Utsumi; Hiroyoshi Suzuki; Masaru Wakatsuki; Kana Kobayashi; Atsushi Okato; Mio Nakajima; Shuri Aoki; Taisuke Sumiya; Tomohiko Ichikawa; Koichiro Akakura; Hiroshi Tsuji; Shigeru Yamada; et al. (Applied Sciences)
Background: The aim of this study was to develop nomograms predicting 5- and 7-year biochemical-recurrence (BCR)-free survival in high-risk prostate cancer (PCa) patients treated with carbon-ion radiotherapy (CIRT) and androgen deprivation therapy (ADT). Methods: We retrospectively evaluated 785 high-risk PCa patients treated with CIRT and ADT. Based on the least absolute shrinkage and selection operator model, two nomograms predicting 5- and 7-year BCR-free survival were developed and internally validated. The ability of each nomogram to predict BCR-free survival was determined by calculating the area under the survival curve (AUC). Results: The 5- and 7-year BCR-free survival rates were 92.1% and 89.3%, respectively. Age, prostate-specific antigen level, clinical T stage, and Gleason score were incorporated into the nomogram predicting 5-year BCR-free survival. In addition to these variables, the percentage of positive biopsy cores was also added to the nomogram predicting 7-year BCR-free survival. The AUC value of each nomogram showed suboptimal-to-good discrimination. Conclusions: We developed the first nomograms accurately predicting BCR-free survival in high-risk PCa patients treated with CIRT and ADT. These nomograms will enable adequate understanding and explanation of BCR-free survival to patients when clinicians use them.